Eksistensi Tanah Ulayat Masyarakat Hukum Adat Dusun Sioma-Oma Dalam Zona Hijau Kehutanan Di Kecamatan Garoga Tapanuli Utara - Sarihot Lubis; Isran Idris; Herlina Manik (Zaaken: Journal of Civil and Business Law, 2022)
This study aims to find out how the existence of the customary law community in Sioma-oma hamlet in the forestry green zone in the Garoga district, North Tapanuli, as well as efforts to protect the law on the customary rights of the Batak customary law community in Sioma-oma hamlet, Garoga district, North Tapanuli. This research is an empirical juridical research which is descriptive qualitative. The results of this study indicate that the existence of the customary law community in the Sioma-oma hamlet is still developing to this day but in terms of obtaining recognition of the forest or customary land it is not carried out properly, especially the existence of the customary law community is still well implemented and is still carrying out various activities. be their customary rights. However, there is still a lack of recognition and protection from the government in the form of laws and regulations governing the existence of the customary law community itself so that the community cannot fully control their customary forest. Efforts made by the customary law community of Sioma-Oma hamlet, Garoga District, North Tapanuli, are to mediate with the government and continue to cultivate their customary land which is one of the routines as the implementation of customary rights. Abstrak Penilitian ini bertujuan untuk mengetahui bagaimana eksistensi tahan ulayat masyarakat hukum adat dusun Sioma-oma dalam zona hijau kehutanan di kecamatan Garoga Tapanuli Utara, serta upaya perlindungan hukum terhadap hak ulayat masyarakat hukum adat batak dusun Sioma-oma kecamatan garoga Tapanuli Utara. Penelitian ini adalah penelitian yuridis empiris yang bersifat deskriptif kualitatif. Hasil dari penelitian ini menunjukan bahwa keberadaan masyarakat hukum adat dusun Sioma-oma masih berkembang eksis hingga saat ini tetapi dalam hal memperoleh pengakuan atas hutan atau tanah adatnya tidak terlaksana dengan baik, terlebih eksistensi mayarakat hukum adat tersebut masih terlaksana dengan baik dan masih melakukan kegiatan yang menjadi hak ulayat mereka. Tetapi masih kurangya pengakuan serta perlindungan dari pemerintah berupa peraturan perundang-undangan yang mengatur tentang keberadaan masyarakat hukum adat itu sendiri sehingga masyarakat tidak dapat menguasai atas hutan adatnya dengan sepenuhnya. Upaya yang dilakukan masyarakat hukum adat dusun Sioma-Oma Kecamatan Garoga Tapanuli Utara adalah dengan cara melakukan mediasi kepada pemerintah dan tetap mengolah tanah adat miliki mereka yang merupakan salah satu rutinitas sebagai pelaksanaan hak ulayat.